Angiotensin Receptor Blockers for Erectile Dysfunction in Hypertensive Men: A Brief Meta-Analysis of Randomized Control Trials. Issue 6 (December 2019) - Ismail, Shaiful Bahari; Noor, Norhayati Mohd; Hussain, Nik Hazlina Nik; Sulaiman, Zaharah; Shamsudin, Muhammad Asyraf; Irfan, Muhammad
Erectile dysfunction is common in adult men, particularly those with hypertension and diabetes. The present study determines the effectiveness of angiotensin receptor blocker (ARB) drugs on erectile function in hypertensive male adults. For this purpose, CENTRAL and MEDLINE and reference lists of the articles were searched. The randomized controlled trials (RCTs) were selected that compared ARBs with conventional therapy or no treatment in men of any ethnicity who were presented with hypertension and/or diabetes. A total four trials that had 2, 809 men were included. Three trials reported adequate random sequence allocation, two reported adequate blinding. Attrition bias is low in one of the included studies. All three studies are of low risk of selective reporting bias. There was an improvement in sexual activity with ARBs (valsartan) (mean difference (MD): 0.71, 95% Confidence Interval (CI) 0.66 to 0.76, I 2 statistic = 0%). However, the erectile functions did not increase significantly in ARBs (losartan or telmisartan) treated men as compared to control or placebo ( n = 203 vs n = 232; MD: 1.36; 95% CI: −0.97 to −3.69; I 2 statistic = 80%). These results suggested that ARBs significantly improved sexual activity among hypertensive men. However, the erectile function was not significantly improved in ARBs treated men as compared to the control or placebo-treated. There were limited studies available. Hence, additional studies are needed to support findings from this review. ARBs should be considered when prescribing antihypertensive drugs to men.